Apakah Model Student Teams Achievement Division (STAD) Berbantuan Media Audiovisual dapat meningkatkan Hasil Belajar yang Optimal? - Sinurat, Oktavila Nauli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low thematic learning outcomes are caused by the limitations in the use of innovative learning models and media. This study aims to analyze the effect of the STAD model combined with audiovisual media on fifth-grade students using a pre-experimental method with a one-group pretest and posttest design. The research subjects consisted of 24 students from the P5 Nias class. Data were collected through multiple-choice test instruments. The analysis results show an improvement in student scores, indicating that the STAD model assisted by audiovisual media has a positive impact on students' cognitive learning outcomes.